AMPHIBIANS - Indraneil, Das; Taha, Wahab; Ramlah, Zainudin (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd., 2025)
The chapter enumerates the amphibian fauna of Niah National Park, Miri, Sarawak.